Scalability Evaluation of the Sentilo Platform Running on Containerized Resources - Domingos, Diogo C. P.; Ismael, Marcelo A. C; Galante, Guilherme; Prasniewski, Eduardo; Assunção, Wesley K. G.; Oyamada, Marcio S.; Bona, Luis C. E. de; Camargo, Edson T. de (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2025: Anais do XXIV Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2025)
A smart city software platform is an integrated environment that helps developers design, implement, deploy, and manage smart city applications. Sentilo is the platform selected to manage smart city solutions in a medium-sized city (Toledo, PR, Brazil) through a partnership between the local university and city administration. This paper aims to evaluate Sentilo’s scalability under different workloads and hardware configurations for both data receiving and provisioning. Results show that Sentilo offers sufficient performance to support the planned and new applications in the city.